REGENERATING TEACHERS’ CAPACITY BUILDING FOR ENTREPRENEURSHIP EDUCATION IN SECONDARY SCHOOLS IN RIVERS STATE AN IMPERATIVE FOR SUSTAINABLE DEVELOPMENT - Dr Joy C. Nzokurum, Adieme, Franca G (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
This study examined regenerating teachers’ capacity building for entrepreneurship education in secondary schools in Rivers State. Three research questions and two null hypotheses guided the study. The study adopted the descriptive research design. The population of the study comprised all the 247 principals and 8,452 teachers in the 247 public secondary schools in Rivers State. A sample size of 1,739 respondents (49 principals and 1,690 teachers) was drawn using the stratified random sampling technique, which represents 20% of the population. A 20-item self-developed questionnaire, which was structured after the four-point modified Likert rating scale was used to collect data from the respondents. The questionnaire was entitled: “Regenerating Teachers’ Capacity Building for Entrepreneurship Skills in Rivers State (RTCBESRS)” and it was duly validated by three experts. The reliability of the questionnaire was tested using test re-test method and was calculated with Pearson’s Product Moment Correlation, which yielded an index of 0.77. Mean and standard deviation were used to answer the research questions while z-test was used to test the null hypotheses of no significant difference. The findings revealed, among others, that regenerating teachers’ capacity building can enhance the teaching of entrepreneurial skills in secondary schools in Rivers State. Based on the findings, it was recommended, among others, that teachers’ capacity building should continually be regenerated or developed in order to keep them abreast of the novel concepts and skills in education.